DETERMINANTS OF SECTORAL LABOR ABSORPTION - Purwantoro Purwantoro; Heffi Christya Rahayu; Arrafiqur Rahman; Hidayat Hidayat (SEAN Institute, 2022)
The island of Java is the region that has the most population in Indonesia compared to other large islands. This situation causes overcrowding and other population problems. One of them is employment. This study aims to see the effect of the population, Provincial Minimum Wage (UMP), and General Allocation Fund (DAU) on the level of labor absorption in Java Island in 2011-2021. The data used is secondary data obtained from the official website of the Indonesian Central Statistics Agency (BPS). In this study using a panel data regression model assisted by the Eviews9 program. The results of this research show that all three independent variables simultaneously have a significant influence on labor absorption. Meanwhile, partially, the population, UMP, and DAU have a positive and significant influence on labor absorption. Control and improvement of the quality of the population is needed to help the level of labor absorption so as not to aggravate the number of unemployed people